The influence of rhizosphere soil microorganisms and environmental factors on gentiopicroside content in the roots and rhizomes of Gentiana scabra Bunge from Liaoning Province - Hou, Jianming; Yin, Haibo; Wang, Dan; Luo, Jiayi; Yang, Wenqi; Kang, Tingguo (Frontiers in Microbiology, 2025)
BackgroundRhizosphere soil microorganisms, as the second genome of plants, play an important role in the formation of secondary metabolites of medicinal plants and are one of the key factors in the formation of the authenticity of medicinal materials.MethodsIn this paper, the rhizosphere soils of Gentiana scabra Bunge from six producing areas in Liaoning Province were taken as the research objects. Through high-throughput sequencing technology, and with the help of PLS-DA and RDA, the impacts of rhizosphere soil microorganisms and environmental factors on the quality of G. scabra were explored in depth.ResultsAlpha diversity shows that the diversity of bacterial communities varies significantly, while the regularity of fungi is weak; beta diversity shows that samples from different producing areas can be effectively grouped according to community structure. LDA effect shows that the differential species of bacteria and fungi vary among different producing areas. Indicator and random forest analysis show that Sphingomonas and Subgroup_2 are the main indicator species of the bacterial communities in the high-content group, which can increase the evenness of microbial communities and maintain or enhance species diversity. The regularity of fungal communities is relatively weak. Functional metagenomic analysis shows that the functions of soil microorganisms in the six producing areas are similar but the relative abundances are different. The main functions of bacteria are closely related to microbial metabolism in diverse environments, biosynthesis of secondary metabolites, metabolic pathways, etc.; fungi are mainly lichen parasite, plant saprotroph, and ericoid mycorrhizal. PLS-DA and RDA analysis show that properly adjusting the key environmental factors of Ca, pH, and rapidly available potassium, which have a great influence on G. scabra, can affect the abundances of microorganisms such as Subgroup_2, Burkholderia-Caballeronia-Paraburkholderia, Metarhizium, Bryobacter, Fusarium, Rhodanobacter, Cladophialophora, Sphingomonas and Trichoderma, and then regulate the content of gentiopicroside.DiscussionThis study provides practical microbial approaches and strategies for improving gentiopicroside content in the roots and rhizomes of G. scabra, and lays a solid scientific foundation for ensuring the quality and safety of genuine medicinal materials and the stable and sustainable development of the G. scabra planting industry.